The United States insurance industry and the growing impact of ride-sharing on automobile insurance - Feshchenko, Anna (2016)
This bachelor thesis discusses the United States Insurance Industry, concentrates on automobile insurance, and shows the impact of ridesharing on it, in form of transportation network companies(TNC). The theoretical part of this paper clarifies the characteristics, structure, and purpose of American insurance regulation, and also describes components of private passenger automobile insurance. As a case study for this paper, an analysis of Uber services is provided, and a breakdown of its commercial insurance is given to look for and discuss gray areas of the coverage and evaluate why they occur. This paper also gives a comparison of California state regulations for transportation network companies with Uber's commercial policy in order to find who is responsible for deficiencies in coverage during the rideshare and what is comprehensive in terms of coverage for rideshare drivers.